2015
DOI: 10.1038/srep12152
|View full text |Cite
|
Sign up to set email alerts
|

The Kallisti Limnes, carbon dioxide-accumulating subsea pools

Abstract: Natural CO2 releases from shallow marine hydrothermal vents are assumed to mix into the water column, and not accumulate into stratified seafloor pools. We present newly discovered shallow subsea pools located within the Santorini volcanic caldera of the Southern Aegean Sea, Greece, that accumulate CO2 emissions from geologic reservoirs. This type of hydrothermal seafloor pool, containing highly concentrated CO2, provides direct evidence of shallow benthic CO2 accumulations originating from sub-seafloor releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…In the back arc basin of the Okinawa Trough a 'lake' of liquid CO 2 accumulates beneath a cap of CO 2 -hydrate (Inagaki et al 2006, Nealson 2006) and at shallower ocean depths pure CO 2 gas is observed to emanate directly from sediments that blanket the margins of hydrothermal vents (figure 1). Pools of liquid CO 2 have been discovered in the Aegean Sea (Camilli et al 2015). Geologic carbon reservoirs such as these are not explicitly included in current marine carbon budgets.…”
Section: Introduction-recent Discoveries and Motivation For This Studymentioning
confidence: 99%
“…In the back arc basin of the Okinawa Trough a 'lake' of liquid CO 2 accumulates beneath a cap of CO 2 -hydrate (Inagaki et al 2006, Nealson 2006) and at shallower ocean depths pure CO 2 gas is observed to emanate directly from sediments that blanket the margins of hydrothermal vents (figure 1). Pools of liquid CO 2 have been discovered in the Aegean Sea (Camilli et al 2015). Geologic carbon reservoirs such as these are not explicitly included in current marine carbon budgets.…”
Section: Introduction-recent Discoveries and Motivation For This Studymentioning
confidence: 99%
“…In the case of KeJ, the possibility that phase separation occurs relatively near the seafloor may facilitate the venting of these brines. Increases in fluid density may also be the result of high levels of dissolved CO 2 as proposed at some other shallow arc volcanoes [ Carey et al ., ; Camilli et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Dissolution of CO 2 after venting has likely lead to decreases in crater water pH as observed at other shallow water volcanic centers with impacts on marine fauna [Hall-Spencer et al, 2008;Tunnicliffe et al, 2009;Carey et al, 2013;Camilli et al, 2015]. Several pH measurements were collected around the Champagne and Shrimp vents using a ROV-deployed pH meter.…”
Section: Gas Dischargementioning
confidence: 99%
“…The exact calibration procedure will vary depending on the system. Here, we present a generic protocol based on those described by various authors (Bell et al, 2007;Schlüter and Gentz, 2008;Wankel et al, 2011;Camilli et al, 2015).…”
Section: Ums System Calibrationmentioning
confidence: 99%